Essere esseri umani. Il coraggio di Mariasilvia Spolato - Giovanni FOCARDI; Nicolò DA LIO; Adriano MANSI (Diacronie. Studi di Storia Contemporanea, 2021)
Mariasilvia Spolato was born in 1935 and died on October 31 2018. Some days later, articles in the media recalled her life, her leading role in the rising Italian homosexual movement and its following oblivion. Even today (June 2021), some web pages dedicated to her and her life still contain a lot of wrong or incomplete information, as some of the videos circulating on the internet are full of mistakes and hagiographic reconstructions. We have two different aims with this paper: 1) to describe more accurately and comprehensively all the phases of Spolato’s life, on the basis of a wide-ranging and different kind of sources (from archives, press and oral testimonies), cross-referencing them with the social and cultural transformations of Italian history; 2) to reflect on the narratives that arose after the news of her disappearance.